Three different causes of hypercalciuria - Skalova, S; Konrad, M; Kutilek, S (Klinische Pädiatrie, 2011)
Hypercalciuria is defined as urinary calcium excretion ≥0.1 mmol/kg/24 h, and can be a result of various disease states. The most frequent clinical signs of hypercalciuria include hematuria, abdominal pain, urolithiasis, nephrocalcinosis, dysuria, enuresis, and urinary tract infection. 3 case reports of children with hypercalciuria of different origin are presented, with final diagnoses of (1)idiopathic hypercalciuria, (2)familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC), and (3)metabolic bone disease of prematurity, respectively. Assessment of hypercalciuria is essential in all children with urolithiasis and nephrocalcinosis, or demineralization of bone. It should be also a part of differential diagnostic procedure in hematuria, recurrent abdominal pain, urinary tract infection and enuresis in childhood.
Keywords: Infant, Low Birth Weight; sekundární hyperparatyreóza; klaudiny; následné studie; Infant, Newborn; Renal Tubular Transport, Inborn Errors; detekce genetických nosičů; Follow-Up Studies; vápník; novorozenec s nízkou porodní hmotností; Genetic Carrier Screening; Male; metabolické nemoci kostí; dítě; hyperkalciurie; novorozenec; Phosphates; Hypercalciuria; vrozené poruchy tubulárního transportu; Alleles; diferenciální diagnóza; mutační analýza DNA; Diagnosis, Differential; předškolní dítě; mužské pohlaví; nefrokalcinóza; kojenec; alely; Hyperparathyroidism, Secondary; nemoci nedonošenců; Child; DNA Mutational Analysis; Calcium; fosfáty; Infant, Premature, Diseases; Kidney Function Tests; Bone Diseases, Metabolic; Claudins; lidé; Humans; Nephrocalcinosis; Child, Preschool; Infant; vyšetření funkce ledvin